Multicenter observational study evaluating the impact of platelet transport bags on product wastage. Issue 5 (11th February 2021) - Kron, Amie; Vijenthira, Shangari; Pendergrast, Jacob; Modi, Dimpy; McLaren, Alyson; MacDonald, Anna; Armali, Chantal; Cserti‐Gazdewich, Christine; Smith, Erica; Quest, Graeme; Gabanowicz, Katie; Lieberman, Lani; et al.
Abstract: Background: Platelets are the most commonly discarded blood product in Canada, with the most common cause of in‐date product loss being improper storage. Transport containers to maintain temperature and extend acceptable return time may represent a method to reduce wastage. The objective of this study was to evaluate the impact of a validated Platelet Transport Bag (PTB) on platelet wastage. Study Design and Methods: Thirty‐six hospitals with the highest platelet discards were invited to participate in a before–after observational study. Hospitals were instructed to utilize a validated 4‐h PTB for clinical situations where immediate transfusion was not planned. Five hospitals audited in‐date platelet discards from July 2018 to November 2019 to characterize wastage causes. In‐date platelet discard data 12 months before and after the start date for each site were analyzed to determine changes in wastage. Results: Of 36 hospital sites, 16 agreed to participate. Pre‐ and postdiscards were 277 and 301, respectively, for all sites combined. There were no significant before–after change in wastage rate (+0.05%, p = .51). Fifty discards were included in the detailed audit; the most common reasons were return to the blood bank after more than 60 min outside a PTB (n = 17, 34%) and return in a red cell cooler (n = 10, 20%). Conclusion: Implementation of PTB did not improve wastage. Common causes of in‐date discards were return after 1 h outside of a PTB and placement in a red cell cooler in error. Further research is required to investigate potential strategies to mitigate in‐date platelet wastage.